Critical Thinking Skills Profile of 7th Grade Junior High School Students on Ecology and Biodiversity Subject - Keliat, Natalia Rosa; Buida, Marshelina Inriani; Hastuti, Susanti Pudji (Bioeducation Journal, 2025)
This research aims to determine the profile of critical thinking skills of Class VII middle school students on ecology and biodiversity material using quantitative descriptive research with data collection techniques using tests, analysis using a quantitative approach consisting of empirical validity, reliability, differentiation, level of difficulty and data analysis scores, and research design using pretest - posttest design, data collection techniques using critical thinking questionnaires, data analysis techniques by looking at interpretation results and N - Gain. The research results of students' critical thinking skills at the beginning of the test (pre-test) reached an average score of 47.49, while the average score of students at the end of learning (posttest) reached 64.09. Based on the interpretation results, it shows that the pre-test results are in the poor category with a total of 63 students (100%), while the post-test scores in the interpretation results show that there are 17 students (26.98%) in the sufficient category and 46 students (73.02%) in the insufficient category. So it can be said that there may be many factors that cause students to lack enthusiasm in science subjects on ecology and biodiversity, including the lack of variety in the methods used in teaching.